Khasiat dan Profil Kromatogram Fraksi Aktif dari Ekstrak Kulit Buah Manggis (Garcinia mangostana L.) yang Diiradiasi - Ermin Katrin; Setiananda Jacobs; Hendig Winarno (Fakultas Farmasi Universitas Pancasila, 2017)
The mangosteen fruit peel (Garcinia mangostana L.) are used as anti-infl ammatory, antihistamine, treatment of heart disease, antibacterial, antifungal, it is also used for the treatment or therapy of cancer, because it has a cytotoxic activity against cancer cells. Most of Indonesian people have used the mangosteen fruit peel and they produce mangosteen peel into powder or herbal medicine industry has produced its extract in capsules. Efforts to preserve dried mangosteen rind has done by heating process or by gamma irradiation technique. This study aimed to study the effect of gamma irradiation on cytotoxicity activity of extracts and active fractions mangosteen fruit peel against L1210 leukemia cells and chromatogram profi le of extracts and active fractions of the mangosteen fruit peel. Dry powder mangosteen rind irradiated using gamma irradiation dose of 5; 7.5; 10; and 15 kGy. Then each sample was successive macerated in n-hexane, ethyl acetate, and ethanol. Each extract was tested cytotoxicity against L1210 leukemia cells. The ethyl acetate extract was most active extract (IC50 = 4.17 mg/mL) compared with n-hexane extract (IC50 = 8.29 mg/mL) and ethanol extract (IC50 = 7.52 mg/mL). Fractionation of ethyl acetate extract by column chromatography were obtained 6 fractions. The result of cytotoxicity test showed that fraction 1 was the most active fraction (IC50 = 3.97 mg/mL), it was it was still categorized as potential anticancer (IC50 ≤ 20 mg/mL). Profi le chromatogram of fraction 1 with TLC-densitometry showed patches of discoloration on irradiation dose of 10 and 15 kGy. The results of analysis by HPLC fraction 1 showed a decrease of peak area at a dose of 10 kGy was signifi cantly different from the control. Based on the chromatogram profi le of fraction 1 and itscytotoxicity against L1210 leukemia cells, so the maximum dose of 7.5 kGy gamma irradiation can beap plied on irradiation of mangosteen fruit peel without changing its effi cacy as anti-cancer agent.